Miejsca traumy w Świecie Miłosza - Kłosiński, Michał (Postscriptum Polonistyczne, 2020)
The author is searching for the spots or cracks through which concealed trauma reveals itself in The World by Miłosz, a text which most of the interpreters described as idyllic. Close reading of Miłosz’s text shows that it is driven by unconscious repression that works to conceal the symptoms of traumatic experience by covering them with a simulation of a housesanctuary. Author is trying to reread The World, paying close attention to these spots and the fact that the date closing the book – April 1943 – is not just an ironic point, but a mark of experience that could not be erased or repressed from memory. The author also points to the intertextual relation between The World and other Miłosz’s texts, and shows how by comparing different types of poetic imagery related to the same memory, one can depict the work of unconscious repression.